Microbiome Compositions From Infertile Couples Seeking In Vitro Fertilization, Using 16S rRNA Gene Sequencing Methods: Any Correlation to Clinical Outcomes? - Okwelogu, Somadina I.; Ikechebelu, Joseph I.; Agbakoba, Nneka R.; Anukam, Kingsley C. (Frontiers in Cellular and Infection Microbiology, 2021)
Background Bacterial infections are usually suspected in infertile couples seeking IVF with no clear understanding of the microbial compositions present in the seminal fluids and vaginal niche of the patients. We used next-generation sequencing technology to correlate microbiota compositions with IVF clinical outcomes. Methods Thirty-six couples were recruited to provide seminal fluids and vaginal swabs. Bacterial DNA was extracted, and V4 region of the 16S rRNA was amplified and sequenced in a pair-end configuration on the Illumina MiSeq platform rendering 2 × 150 bp sequences. Microbial taxonomy to species level was generated using the Greengenes database. Linear discriminant analysis (LDA) effect size (LEfSe) was used to identify biologically and statistically significant differences in relative abundance. Results Seminal fluid microbiota compositions had lower bacterial concentrations compared with the vagina, but species diversity was significantly higher in seminal fluid samples. Azoospermic subjects had more relative abundance of Mycoplasma and Ureaplasma. In Normospermic semen, Lactobacillus (43.86%) was the most abundant, followed by Gardnerella (25.45%), while the corresponding vaginal samples, Lactobacillus (61.74%) was the most abundant, followed by Prevotella (6.07%) and Gardnerella (5.86%). Conclusions Semen samples with positive IVF were significantly colonized by Lactobacillus jensenii (P=0.002), Faecalibacterium (P=0.042) and significantly less colonized by Proteobacteria, Prevotella, Bacteroides, and lower Firmicutes/Bacteroidetes ratio compared with semen samples with negative IVF. Vaginal samples with positive IVF clinical outcome were significantly colonized by Lactobacillus gasseri, less colonized by Bacteroides and Lactobacillus iners. This study has opened a window of possibility for Lactobacillus replenishments in men and women before IVF treatment.